A zinc metal negative electrode interface layer protective film and a preparation method and application thereof
Patent Information
- Application Number
- CN202510926474.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-07
- Publication Date
- 2026-10-30
AI Technical Summary
但在实际使用过程中,由于Zn箔加工工艺的限制,往往伴随着化学成分不均匀和形状不规整等缺陷,导致Zn箔各处的表面电场和电化学反应电位不相同
[0060]1、本申请提供的保护膜由进行阳离子交换后的质子交换膜和磁控溅射金属层所组成。阳离子交换后的质子交换膜表面会形成离子传输通道,加速锌离子的传输速率,诱导锌离子快速、均匀沉积,减少局部过度沉积,从源头抑制锌枝晶的形成,同时由于聚合物分子链本身疏水,从而能诱导锌离子定向通过离子传输通道进行选择性沉积,在减少锌枝晶形成的同时还能抑制HER副反应和副产物的生成,提高库伦效率;同时其本身的力学强度和化学稳定性也能抑制锌枝晶的生成,延长电池的有效循环寿命。而磁控溅射金属镀层可以在锌沉积过程中与其发生合金化,降低锌沉积的能垒、进一步减少锌金属的不均匀沉积和枝晶生成。将此人工锌负极保护膜作为AZIB的负极保护层材料,可以大大提高电池的循环寿命和充放电性能。
Smart Images

Figure CN123017845A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery technology, and relates to a zinc metal anode interface layer protective film, its preparation method, and its application. Background Technology
[0002] With the continued growth of global energy demand and increasingly stringent carbon emission restrictions, rechargeable batteries are considered a key technology for reducing dependence on fossil fuels and the greenhouse effect, as well as an effective solution for the large-scale utilization of renewable energy. For a long time, lithium-ion batteries (LIBs) have been widely regarded by the scientific community as one of the most promising portable energy storage device options due to their good theoretical capacity and superior energy density. However, the inherent organic electrolytes of LIBs inevitably bring potential safety issues due to their flammable, explosive, and potentially toxic properties. At the same time, the relative scarcity of lithium resources on Earth leads to the high cost of LIBs, limiting their further widespread use.
[0003] Against this backdrop, zinc-ion batteries (ZIBs) have come into the view of researchers. Compared to LIBs, ZIBs have a series of unique advantages, mainly including: ① Zinc, as a multivalent metal, combined with its high density, gives ZIBs a more ideal volumetric energy density (5,851 mAh·cm³). -3 It is LIBs (2,061 mAh·cm⁻¹) -3 (nearly three times); ② Zinc anodes have a lower redox potential (-0.76V vs SHE) and stronger corrosion resistance, and can be used with both aqueous and non-aqueous electrolytes. Among them, ZIBs using aqueous electrolytes not only have a higher oxidation-reduction potential than organic electrolytes (1-10mS·cm) but also have a lower oxidation-reduction potential (-0.76V vs SHE) and stronger corrosion resistance, and can be used with both aqueous and non-aqueous electrolytes. -1 Two orders of magnitude higher ionic conductivity (reaching 1 S·cm) -1 Furthermore, aqueous zinc-ion batteries (AZIBs) possess significant advantages such as being non-flammable and non-explosive, non-toxic and harmless, and low in cost. For these reasons, many industry experts consider AZIBs to be an ideal choice for next-generation energy storage technology, particularly in stationary energy storage fields such as peak shaving and valley filling, wind and solar power energy storage, peak-valley arbitrage, and backup power.
[0004] However, because AZIBs use aqueous electrolytes, which are rarely used in traditional secondary batteries, a series of new problems have arisen, mainly including: the narrow electrochemical stability window of aqueous electrolytes, limiting the battery's operating voltage; the easy dissolution of some cathode materials, leading to capacity decay; and Zn... 2+Strong electrostatic repulsion limits the kinetics of Zn foil insertion into the positive electrode; desolvation occurs at the electrode-electrolyte interface; dendrite growth in the Zn metal negative electrode and the formation of hydrogen evolution reaction (HER) and ZnO and Zn(OH)2 byproducts lead to a decrease in coulombic efficiency (CE). Although theoretically, AZIBs can directly use pure Zn foil as the negative electrode, in practical applications, limitations in Zn foil processing often result in defects such as inhomogeneous chemical composition and irregular shape, leading to inconsistent surface electric fields and electrochemical reaction potentials at different locations on the Zn foil. This, in turn, causes Zn... 2+ The adsorption of Zn on the Zn foil surface is uneven, with some areas showing Zn adsorption. 2+ Extensive and concentrated deposition of Zn leads to dendrite formation. Dendrite formation not only reduces the reversibility of AZIBs cycling but can also cause battery puncture, rendering the battery unusable. Furthermore, the kinetics of the Zn anode-electrolyte interface affect not only the smoothness of the electrochemical reaction but also the formation of side reactions and byproducts at the reaction interface, thus impacting the coulombic efficiency during cycling. Therefore, achieving uniform and dense Zn deposition, overcoming the Zn dendrite problem, and realizing efficient ion transport at the Zn anode-electrolyte interface are essential prerequisites for AZIBs to move beyond the laboratory and achieve commercialization. Summary of the Invention
[0005] To address the aforementioned problems in the prior art, the present invention aims to provide a zinc metal anode interface layer protective film, its preparation method, and its application, thereby overcoming the shortcomings of the prior art. The present invention employs the following technical solutions to achieve its objective:
[0006] One aspect of the present invention provides a zinc metal anode interface layer protective film, the protective film comprising: at least one proton exchange membrane that has undergone pretreatment and cation exchange treatment, and a metal layer located on the surface of the proton exchange membrane.
[0007] Preferably, the proton exchange membrane is selected from one or more of perfluorosulfonic acid proton exchange membranes, partially fluorinated proton exchange membranes, non-fluorinated sulfonic acid proton exchange membranes, and composite-enhanced proton exchange membranes.
[0008] Perfluorosulfonic acid proton exchange membranes can be listed as one or more of the following: Nafion (sulfonated tetrafluorovinyl fluoropolymer copolymer), Dow ultrafiltration / reverse osmosis membranes, Xus-B204 membranes, 3M PFSA membranes, Fumapem membranes, Solef PVDF membranes, Aquivion membranes, DF988 membranes, DF2801 membranes, Alciplex membranes, Flemion membranes, and C-series membranes.
[0009] Partially fluorinated proton exchange membranes can be listed as BAM membranes (partially fluorinated polystyrene PEM), sulfonated grafted polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), tetrafluoroethylene and hexafluoropropylene copolymer (FEP), or ethylene-tetrafluoroethylene copolymer (ETFE), etc.
[0010] Non-fluorinated sulfonic acid proton exchange membranes can be listed as one or more of the following: sulfonated styrene-butadiene / styrene block copolymer membrane, sulfonated polyaryletherketone, phosphoric acid-doped polybenzimidazole (PBI), polyethersulfone (PES), sulfonated polysulfide sulfone (SPAES), polyether ether ketone (PEEK), sulfonated polyether ether ketone (SPEEK), sulfonated diazanaphthalene polyether sulfone ketone, sulfonated polyimide (SPI), and sulfonated polybenzimidazole.
[0011] Composite reinforced proton exchange membranes include Gore-Select, NASTA / NASTAH series heteropolyacid blend membranes, Solef PVDF, proton exchange membranes obtained by modifying the above proton exchange membrane materials with inorganic oxide particles (such as SiO2, CeO2, ZrO2, TiO2, etc.), metal nanoparticles (such as Pt), carbon materials (such as carbon fibers, carbon nanotubes, graphene, etc.), and composite membranes formed by combining the above proton exchange membranes with a porous membrane support substrate of polytetrafluoroethylene (PTFE) or polyethylene (PE).
[0012] More preferably, the proton exchange membrane is selected from one or more of the Nafion series of perfluorosulfonic acid membranes.
[0013] Further preferred, the proton exchange membrane is Nafion NC700.
[0014] The pretreatment of the proton exchange membrane and the cation exchange treatment were carried out sequentially.
[0015] Preferably, the pretreatment includes: placing the proton exchange membrane in an aqueous hydrogen peroxide solution and heating it to remove impurities from the surface, then removing the membrane and heating it in water to remove any remaining aqueous hydrogen peroxide solution from the surface.
[0016] The minimum standard for the amount of hydrogen peroxide solution and water is that the liquid volume should submerge all areas of the proton exchange membrane.
[0017] Optionally, the mass fraction of the hydrogen peroxide aqueous solution is 0.5–30 wt%.
[0018] The two heating steps are heated at temperatures of 40–100℃ and for 1–4 hours respectively.
[0019] Preferably, the pretreatment steps are as follows: placing the proton exchange membrane in a 1-10 wt% hydrogen peroxide aqueous solution and heating it in a silicone oil bath at 60-90°C for 1-3 hours; then placing the impurity-removed proton exchange membrane in deionized water and heating it in a silicone oil bath at 60-90°C for 1-3 hours.
[0020] Preferably, the cation exchange treatment includes: immersing the pretreated proton exchange membrane in a cation exchange solution for several hours; after the cation exchange is completed, washing off any remaining solution on the surface with water and drying.
[0021] The minimum required volume of cation exchange solution is: the liquid volume must submerge all areas of the proton exchange membrane.
[0022] Optionally, the cation exchange solution A is formed by dissolving a solute in water, and the solute may be one or more of metal hydroxides, metal salts, metal halides, and metal sulfides.
[0023] Preferably, the metal in the metal hydroxide, metal salt, metal halide, or metal sulfide is selected from one or more of lithium, sodium, magnesium, potassium, calcium, manganese, iron, cobalt, nickel, copper, zinc, and silver.
[0024] The metal salt is selected from one or more of the following metals: nitrates, sulfates, acetates, formates, phosphates, oxalates, borates, citrates, niobates, tetrafluoroborate, difluorooxalate borate, perchlorates, hexafluorophosphates, trifluoromethanesulfonates, iodates, bis(fluorosulfonyl)imide salts, arsenates, carbonates, and tantalates.
[0025] The metal halide is selected from one or more of the chloride, fluoride, bromide, and iodide of the metal.
[0026] Preferably, the solute in the cation exchange solution is one or more of LiOH, NaOH, and KOH.
[0027] More preferably, the solute is NaOH.
[0028] Preferably, the concentration of the cation exchange solution is 0.1–5 mol / L.
[0029] Preferably, the soaking time is 12 to 72 hours.
[0030] Preferably, the drying temperature is 40–100°C and the drying time is 12–48 hours, which can be carried out in a forced-air drying oven.
[0031] Preferably, the cation exchange treatment specifically includes: immersing the pretreated proton exchange membrane in a cation exchange solution with a concentration of 1-3 mol / L for 30-60 hours; after the cation exchange is completed, washing off any residual solution on the surface with water; and drying at 50-80°C for 18-30 hours.
[0032] Preferably, the metal layer is formed from one or more of Al, Al-Si, Cu, Al-Si-Cu, Au, Au alloy, Ag, In, Fe, Co, Ni, Mn, Fe-Mn, Fe-Ni, Mg, Sn, Pb, Bi, Sb, Ti, Te, Zr, and Zn.
[0033] More preferably, the metal layer is formed from one or more of Al, In, Sn, Cu, Bi, Sb, Mg, Ni, and Mn.
[0034] Further preferably, the metal layer is formed of In.
[0035] The metal layer is obtained by magnetron sputtering, which includes the following steps:
[0036] In a vacuum environment, a magnetron sputtering target is excited under a certain pressure using a radio frequency power supply of a certain power. After a period of time, a uniform and dense metal film can be formed on the surface of the proton exchange membrane after cation exchange.
[0037] Optionally, the vacuum environment pressure is 0.1 to 9 × 10⁻⁶. -4 Pa.
[0038] Optionally, the power of the radio frequency power supply is 10 to 150 W, and the sputtering pressure is 0.1 to 1.0 Pa.
[0039] Optionally, the magnetron sputtering duration is 0.5 to 5 hours.
[0040] Preferably, the magnetron sputtering target is made of one or more alloys formed from Al, Al-Si, Cu, Al-Si-Cu, Au, Au alloy, Ag, In, Fe, Co, Ni, Mn, Fe-Mn, Fe-Ni, Mg, Sn, Pb, Bi, Sb, Ti, Te, Zr, and Zn.
[0041] Further preferably, the magnetron sputtering target is made of an alloy formed from one or more of Al, In, Sn, Cu, Bi, Sb, Mg, Ni, and Mn.
[0042] Preferably, the purity of the magnetron sputtering target material is ≥99.9%.
[0043] Preferably, the magnetron sputtering specifically includes: 0.1 to 9 × 10⁻⁶-4 In a vacuum environment of Pa, a radio frequency power supply with a power of 20 to 100 W is used to excite the magnetron sputtering target at a sputtering pressure of 0.2 to 0.8 Pa for a sputtering time of 1 to 3 hours.
[0044] A second aspect of this invention provides a method for preparing a protective film at the interface of a zinc metal anode, comprising the following steps:
[0045] The proton exchange membrane was heated in a hydrogen peroxide aqueous solution, then removed and heated in water again. After removing the surface moisture of the proton exchange membrane, it was immersed in a cation exchange solution. After cation exchange was completed, it was cleaned and dried. In a vacuum environment, a magnetron sputtering target was excited by a radio frequency power supply to form a metal layer on the surface of the proton exchange membrane after cation exchange.
[0046] Preferably, the preparation method specifically includes the following steps:
[0047] The proton exchange membrane was placed in a 1–10 wt% hydrogen peroxide aqueous solution and heated in a silicone oil bath at 60–90 °C for 1–3 h. After purification, the proton exchange membrane was placed in deionized water and heated in a silicone oil bath at 60–90 °C for 1–3 h. After removing the membrane and removing surface moisture, it was immersed in a 1–3 mol / L cation exchange solution for 30–60 h. After cation exchange, the membrane was washed with water to remove any remaining solution and dried at 50–80 °C for 18–30 h. The membrane was then dried in a 0.1–9 × 10⁻⁶ solution. -4 In a vacuum environment of Pa, a radio frequency power supply with a power of 20 to 100 W is used to excite the magnetron sputtering target at a sputtering pressure of 0.2 to 0.8 Pa for a sputtering time of 1 to 3 hours.
[0048] A third aspect of the present invention provides an aqueous zinc-ion battery, the aqueous zinc-ion battery comprising at least one of the above-described protective films.
[0049] Preferably, the aqueous zinc-ion battery is a half-cell or a full-cell aqueous zinc-ion battery.
[0050] In the aqueous zinc-ion battery half-cell, the protective film is located between the negative electrode and the separator, and / or between the current collector and the separator.
[0051] In the aforementioned aqueous zinc-ion battery, the protective film is located between the negative electrode and the separator, with the side of the protective film having the metal layer facing the electrode. That is, the side of the protective film with the metal layer is in contact with the electrode.
[0052] The aqueous zinc-ion battery half-cell includes a current collector, a protective membrane, a separator, an electrolyte, and a zinc negative electrode; the aqueous zinc-ion battery full-cell includes a positive electrode, a separator, an electrolyte, a protective membrane, and a zinc negative electrode.
[0053] There are no particular restrictions on the current collector material. For example, it may be selected from one or more of the following components: copper, copper alloy, aluminum, aluminum alloy, nickel, nickel alloy, stainless steel, carbon materials, and composite current collector.
[0054] Copper and its alloys, including copper foil, copper mesh or copper foam; aluminum and its alloys, including aluminum foil or etched honeycomb aluminum; nickel and its alloys, including nickel foil or nickel foam; stainless steel, including stainless steel mesh or porous stainless steel; carbon materials, including graphene, carbon fiber cloth or carbon nanotubes; composite current collectors, including conductive resins, carbon-coated aluminum foil or titanium-nickel shape memory alloys.
[0055] There are no particular restrictions on the positive electrode material in the positive electrode sheet. For example, it can be selected from one or more of the following components: (1) manganese (Mn)-based compounds, such as α-MnO2, β-MnO2, γ-MnO2, α-Mn2O3, α-Mn3O4, ZnMn2O4, etc.; (2) vanadium (V)-based compounds, such as VO2, V2O5, V3O7·H2O, V6O 13 V 10 O 24 ·12H2O, VS2, H2V3O8, LiV3O8, Zn 0.25 V2O5·nH2O, Zn2V2O7, Zn3V2O7(OH)2·2H2O, Ca 0.25 V₂O₅·nH₂O, Na₂V₆O 16 ·3H2O, etc.; (3) Prussian blue analogues, with the molecular formula A x M Ay [M B (CN)6] z ·nH2O (where A represents an alkali metal, M A and M B (4) Transition metals, such as Mn, Fe, Co, Ni, Cu and Zn; (5) Lithium or sodium ion intercalation materials, such as LiMn2O4, LiMn 0.8 Fe 0.2 PO4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, Na3V2(PO4)2F3, Na3V2(PO4)3 / C, etc.; (5) Nickel (Ni) or cobalt (Co) based materials, such as NiO, Ni3S2, Ni(OH)2, NiCo2O4, Co3O4@NiO, NiAlCo layered double hydroxides and Co3O4, etc.; (6) Organic materials, such as conductive polymers polyaniline (PANI), polypyrrole (PPy), etc.; (7) Bifunctional air electrode materials for zinc-air batteries, etc.
[0056] There are no special restrictions on the diaphragm material. For example, it can be a glass fiber diaphragm, a polyethylene diaphragm, a polypropylene diaphragm, or a polyethylene / polypropylene composite multilayer diaphragm.
[0057] The electrolyte comprises a zinc salt and water, wherein the zinc salt is selected from one or more of ZnSO4, Zn(NO3)2, Zn(CH3COO)2, ZnF2, Zn(ClO4)2, ZnCl2, Zn(TFSI)2 and Zn(CF3SO3)2.
[0058] Preferably, the concentration of the zinc salt in the electrolyte is 0.1–20 mol / L, more preferably 0.5–5 mol / L.
[0059] Compared with the prior art, the present invention has the following beneficial effects:
[0060] 1. The protective film provided in this application consists of a proton exchange membrane after cation exchange and a magnetron sputtered metal layer. The surface of the proton exchange membrane after cation exchange forms ion transport channels, accelerating the transport rate of zinc ions, inducing rapid and uniform deposition of zinc ions, reducing localized over-deposition, and inhibiting the formation of zinc dendrites from the source. Simultaneously, due to the hydrophobic nature of the polymer molecular chains, zinc ions can be selectively deposited through the ion transport channels, reducing zinc dendrite formation while also inhibiting HER side reactions and byproducts, thus improving coulombic efficiency. Furthermore, its mechanical strength and chemical stability also inhibit zinc dendrite formation, extending the effective cycle life of the battery. The magnetron sputtered metal coating can alloy with zinc during the deposition process, lowering the energy barrier for zinc deposition and further reducing uneven zinc metal deposition and dendrite formation. Using this artificial zinc negative electrode protective film as the negative electrode protective layer material for AZIB can significantly improve the battery's cycle life and charge / discharge performance.
[0061] 2. Proton exchange membranes treated with NaOH for cation exchange exhibit better overall electrochemical performance than membranes treated with LiOH or KOH, showing longer cycle life, higher coulombic efficiency, and better capacity retention.
[0062] 3. An In metal layer is formed on the surface of a proton exchange membrane by magnetron sputtering, exhibiting superior overall performance compared to many other metals.
[0063] 4. Overall, the proton exchange membrane treated with NaOH for cation exchange, with an In metal layer formed on its surface by magnetron sputtering, forms an In-Na protective film in the aqueous zinc-ion battery. In the half-cell cycle, it combines the advantages of the cation exchange membrane and the magnetron sputtering coating, exhibiting advantages such as long cycle life, high coulombic efficiency, and low polarization voltage. In the full-cell cycle, it also exhibits advantages such as stable coulombic efficiency and high capacity retention. Attached Figure Description
[0064] Figure 1 The images are of In-Na@Nafion in Example 1, (a) is the front (sputtered surface), and (b) is the back.
[0065] Figure 2 The images show the FTIR spectra of In-Na@Nafion in Example 1 and Na@Nafion in Comparative Example 2.
[0066] Figure 3 The cycling coulombic efficiency diagram of the Zn-Cu half-cell with In-Na@Nafion added in Example 1;
[0067] Figure 4 The first-cycle polarization voltage-capacity curve of the Zn-Cu half-cell with In-Na@Nafion added in Example 1.
[0068] Figure 5 The diagram shows the cycle coulombic efficiency and specific capacity of the Zn-I2 / PAC full cell with In-Na@Nafion added in Example 1. Detailed Implementation
[0069] The technical solution of the present invention will be further described and illustrated below with reference to specific embodiments and accompanying drawings. It should be understood that the specific embodiments described herein are only for the purpose of helping to understand the present invention and are not intended to limit the specific scope of the present invention. Furthermore, the accompanying drawings used herein are merely for better illustrating the content disclosed in the present invention and do not limit the scope of protection. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used in the art, and the methods used in the embodiments are all conventional methods in the art.
[0070] In the description of this invention, unless otherwise stated, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, and includes both a and b. "Multiple" includes two, three, four, five, or more.
[0071] Comparative Example 1
[0072] The protective film of Comparative Example 1 was prepared by the following steps:
[0073] S1. Cut Nafion NC700 (15μm thickness) to 60mm×60mm and peel off the surface film and bottom film of Nafion; place Nafion in a silicone oil bath at 80℃ and 5wt% H2O2 aqueous solution for 1h to remove organic impurities on the surface; rinse repeatedly with deionized water and then place in a silicone oil bath at 80℃ and deionized water for 1h to remove residual H2O2.
[0074] S2. After the Nafion surface has been treated with a dust-free paper, absorb the water and place it in 20 mL of deionized water for 48 h. After taking it out, wash it three times with deionized water and dry it in a 60℃ forced-air drying oven for 24 h to obtain a blank Nafion protective film.
[0075] Comparative Example 2
[0076] The protective film of Comparative Example 2 was prepared by the following steps:
[0077] Step S1 is the same as Comparative Example 1;
[0078] S2. After the water on the surface of Nafion was treated with lint-free paper, it was placed in 20 mL of 2 mol / L NaOH (aq) and left to stand for 48 h. After taking it out, it was washed three times with deionized water and dried in a 60℃ convection drying oven for 24 h to obtain Na@Nafion protective film.
[0079] Comparative Example 3
[0080] The protective film of Comparative Example 3 was prepared by the following steps:
[0081] Step S1 is the same as Comparative Example 1;
[0082] S2. After the water on the surface of Nafion was treated with lint-free paper, it was placed in 20 mL of 2 mol / L LiOH (aq) and left to stand for 48 h. After taking it out, it was washed three times with deionized water and dried in a 60℃ convection drying oven for 24 h to obtain Na@Nafion protective film.
[0083] Comparative Example 4
[0084] The protective film of Comparative Example 4 was prepared by the following steps:
[0085] Step S1 is the same as Comparative Example 1;
[0086] S2. After the Nafion surface was treated with lint-free paper, it was placed in 20 mL of 2 mol / L KOH (aq) and left to stand for 48 h. After taking it out, it was washed three times with deionized water and dried in a 60℃ convection drying oven for 24 h to obtain the Na@Nafion protective film.
[0087] Comparative Example 5
[0088] The protective film of Comparative Example 5 was prepared by the following steps:
[0089] S1. Cut Nafion NC700 to 60mm×60mm and peel off the surface film and bottom film of Nafion; place Nafion in a silicone oil bath at 80℃ and 5wt% H2O2 aqueous solution for 1 hour to remove organic impurities on the surface; rinse repeatedly with deionized water and then place in a silicone oil bath at 80℃ and deionized water for 1 hour to remove residual H2O2.
[0090] S2. After the Nafion surface has been treated with a dust-free paper, absorb the water and place it in 20 mL of deionized water for 48 h. After taking it out, wash it three times with deionized water and dry it in a 60℃ drying oven for 24 h to obtain a blank Nafion protective film.
[0091] S3. Place the dried blank Nafion protective film under an air pressure of less than 4 × 10⁻⁶. -4 In a high vacuum environment of Pa, using a 50W RF power supply and a high-purity (99.99%) In target, magnetron sputtering was performed for 2 hours at a sputtering pressure of 0.5Pa to obtain a modified In-Nafion protective film.
[0092] Comparative Example 6
[0093] The difference between Comparative Example 6 and Comparative Example 5 is that in step S3 of Comparative Example 6, a high-purity (99.99%) Al target material is used to replace the high-purity (99.99%) In target material of Comparative Example 5 to obtain the modified Al-Nafion protective film.
[0094] Comparative Example 7
[0095] The difference between Comparative Example 7 and Comparative Example 5 is that in step S3 of Comparative Example 7, a high-purity (99.99%) Sn target is used to replace the high-purity (99.99%) In target of Comparative Example 5 to obtain the modified Sn-Nafion protective film.
[0096] Comparative Example 8
[0097] The difference between Comparative Example 8 and Comparative Example 5 is that in step S3 of Comparative Example 8, a high-purity (99.99%) Cu target is used to replace the high-purity (99.99%) In target of Comparative Example 5 to obtain a modified Cu-Nafion protective film.
[0098] Comparative Example 9
[0099] The difference between Comparative Example 9 and Comparative Example 5 is that in step S3 of Comparative Example 9, a high-purity (99.99%) Bi target material is used to replace the high-purity (99.99%) In target material of Comparative Example 5 to obtain the modified Bi-Nafion protective film.
[0100] Comparative Example 10
[0101] The difference between Comparative Example 10 and Comparative Example 5 is that in step S3 of Comparative Example 10, a high-purity (99.99%) Sb target was used to replace the high-purity (99.99%) In target of Comparative Example 5 to obtain the modified Sb-Nafion protective film.
[0102] Comparative Example 11
[0103] The difference between Comparative Example 11 and Comparative Example 5 is that in step S3 of Comparative Example 11, a high-purity (99.99%) Mg target is used to replace the high-purity (99.99%) In target of Comparative Example 5 to obtain a modified Mg-Nafion protective film.
[0104] Comparative Example 12
[0105] The difference between Comparative Example 12 and Comparative Example 5 is that in step S3 of Comparative Example 12, a high-purity (99.99%) Ni target is used to replace the high-purity (99.99%) In target of Comparative Example 5 to obtain the modified Ni-Nafion protective film.
[0106] Comparative Example 13
[0107] The difference between Comparative Example 13 and Comparative Example 5 is that in step S3 of Comparative Example 13, a high-purity (99.99%) Mn target material is used to replace the high-purity (99.99%) In target material of Comparative Example 5 to obtain a modified Mn-Nafion protective film.
[0108] Example 1
[0109] The protective film in this embodiment is prepared by the following method:
[0110] S1. Cut Nafion NC700 to 60mm×60mm and peel off the surface film and bottom film of Nafion; place Nafion in a silicone oil bath at 80℃ and 5wt% H2O2 aqueous solution for 1 hour to remove organic impurities on the surface; rinse repeatedly with deionized water and then place in a silicone oil bath at 80℃ and deionized water for 1 hour to remove residual H2O2.
[0111] S2. After the water on the surface of Nafion was treated with lint-free paper, it was placed in 20 mL of 2 mol / L NaOH (aq) and left to stand for 48 h. After taking it out, it was washed three times with deionized water and dried in a 60℃ drying oven for 24 h to obtain Na@Nafion protective film.
[0112] S3. The dried Na@Nafion protective film is then subjected to an air pressure of less than 4×10⁻⁶. -4In a high vacuum environment of Pa, using a 50W RF power supply and a high-purity (99.99%) In target, magnetron sputtering was performed for 2 hours at a sputtering pressure of 0.5Pa to obtain the modified In-Na@Nafion protective film.
[0113] Example 2
[0114] The difference between Example 2 and Example 1 is that in Example 2, step S3 uses a high-purity (99.99%) Al target instead of the high-purity (99.99%) In target of Example 1 to obtain a modified Al-Na@Nafion protective film.
[0115] Example 3
[0116] The difference between Example 3 and Example 1 is that in Example 3, step S3 uses a high-purity (99.99%) Sn target to replace the high-purity (99.99%) In target of Example 1, resulting in a modified Sn-Na@Nafion protective film.
[0117] Example 4
[0118] The difference between Example 4 and Example 1 is that in Example 4, step S3 uses a high-purity (99.99%) Cu target material instead of the high-purity (99.99%) In target material of Example 1 to obtain a modified Cu-Na@Nafion protective film.
[0119] Example 5
[0120] The difference between Example 5 and Example 1 is that in Example 5, step S3 uses a high-purity (99.99%) Bi target material instead of the high-purity (99.99%) In target material of Example 1 to obtain a modified Bi-Na@Nafion protective film.
[0121] Example 6
[0122] The difference between Example 6 and Example 1 is that in Example 6, step S3 uses a high-purity (99.99%) Sb target instead of the high-purity (99.99%) In target of Example 1 to obtain a modified Sb-Na@Nafion protective film.
[0123] Example 7
[0124] The difference between Example 7 and Example 1 is that in Example 7, step S3 uses a high-purity (99.99%) Mg target instead of the high-purity (99.99%) In target of Example 1 to obtain a modified Mg-Na@Nafion protective film.
[0125] Example 8
[0126] The difference between Example 8 and Example 1 is that in Example 8, step S3 uses a high-purity (99.99%) Ni target instead of the high-purity (99.99%) In target of Example 1 to obtain a modified Ni-Na@Nafion protective film.
[0127] Example 9
[0128] The difference between Example 9 and Example 1 is that in Example 9, step S3 uses a high-purity (99.99%) Mn target to replace the high-purity (99.99%) In target of Example 1 to obtain a modified Mn-Na@Nafion protective film.
[0129] Example 10
[0130] The protective film in this embodiment is prepared by the following method:
[0131] S1. Cut Nafion NC700 to 60mm×60mm and peel off the surface film and bottom film of Nafion; place Nafion in a silicone oil bath at 80℃ and 5wt% H2O2 aqueous solution for 1 hour to remove organic impurities on the surface; rinse repeatedly with deionized water and then place in a silicone oil bath at 80℃ and deionized water for 1 hour to remove residual H2O2.
[0132] S2. After the water on the surface of Nafion was treated with lint-free paper, it was placed in 20 mL of 2 mol / L LiOH (aq) and left to stand for 48 h. After taking it out, it was washed three times with deionized water and dried in a 60℃ forced-air drying oven for 24 h to obtain Li@Nafion protective film.
[0133] S3. The dried Li@Nafion protective film is then subjected to an air pressure of less than 4×10⁻⁶. -4 In a high vacuum environment of Pa, using a 50W RF power supply and a high-purity (99.99%) In target, magnetron sputtering was performed for 2 hours at a sputtering pressure of 0.5Pa to obtain the modified In-Li@Nafion protective film.
[0134] Example 11
[0135] The difference between Example 11 and Example 10 is that in step S3 of Example 11, a high-purity (99.99%) Al target is used instead of the high-purity (99.99%) In target of Example 10 to obtain a modified Al-Li@Nafion protective film.
[0136] Example 12
[0137] The difference between Example 12 and Example 10 is that in step S3 of Example 12, a high-purity (99.99%) Sn target is used instead of the high-purity (99.99%) In target of Example 10 to obtain a modified Sn-Li@Nafion protective film.
[0138] Example 13
[0139] The difference between Example 13 and Example 10 is that in Example 13, step S3 uses a high-purity (99.99%) Cu target material instead of the high-purity (99.99%) In target material of Example 10 to obtain a modified Cu-Li@Nafion protective film.
[0140] Example 14
[0141] The difference between Example 14 and Example 10 is that in step S3 of Example 14, a high-purity (99.99%) Bi target is used instead of the high-purity (99.99%) In target of Example 10 to obtain a modified Bi-Li@Nafion protective film.
[0142] Example 15
[0143] The difference between Example 15 and Example 10 is that in step S3 of Example 15, a high-purity (99.99%) Sb target is used instead of the high-purity (99.99%) In target of Example 10 to obtain a modified Sb-Li@Nafion protective film.
[0144] Example 16
[0145] The difference between Example 16 and Example 10 is that in step S3 of Example 16, a high-purity (99.99%) Mg target is used instead of the high-purity (99.99%) In target of Example 10 to obtain a modified Mg-Li@Nafion protective film.
[0146] Example 17
[0147] The difference between Example 17 and Example 10 is that in Example 17, step S3 uses a high-purity (99.99%) Ni target instead of the high-purity (99.99%) In target of Example 10 to obtain a modified Ni-Li@Nafion protective film.
[0148] Example 18
[0149] The difference between Example 18 and Example 10 is that in Example 18, step S3 uses a high-purity (99.99%) Mn target instead of the high-purity (99.99%) In target of Example 10 to obtain a modified Mn-Li@Nafion protective film.
[0150] Example 19
[0151] The protective film in this embodiment is prepared by the following method:
[0152] S1. Cut Nafion NC700 to 60mm×60mm and peel off the surface film and bottom film of Nafion; place Nafion in a silicone oil bath at 80℃ and 5wt% H2O2 aqueous solution for 1 hour to remove organic impurities on the surface; rinse repeatedly with deionized water and then place in a silicone oil bath at 80℃ and deionized water for 1 hour to remove residual H2O2.
[0153] S2. After the water on the surface of Nafion was treated with lint-free paper, it was placed in 20 mL of 2 mol / L KOH (aq) and left to stand for 48 h. After taking it out, it was washed three times with deionized water and dried in a 60℃ forced-air drying oven for 24 h to obtain K@Nafion protective film.
[0154] S3. The dried Li@Nafion protective film is then subjected to an air pressure of less than 4×10⁻⁶. -4 In a high vacuum environment of Pa, using a 50W RF power supply and a high-purity (99.99%) In target, magnetron sputtering was performed for 2 hours at a sputtering pressure of 0.5Pa to obtain the modified In-K@Nafion protective film.
[0155] Example 20
[0156] The difference between Example 20 and Example 19 is that in step S3 of Example 20, a high-purity (99.99%) Al target is used instead of the high-purity (99.99%) In target of Example 19 to obtain a modified Al-K@Nafion protective film.
[0157] Example 21
[0158] The difference between Example 21 and Example 19 is that in Example 21, step S3 uses a high-purity (99.99%) Sn target to replace the high-purity (99.99%) In target of Example 19, resulting in a modified Sn-K@Nafion protective film.
[0159] Example 22
[0160] The difference between Example 22 and Example 19 is that in step S3 of Example 22, a high-purity (99.99%) Cu target is used instead of the high-purity (99.99%) In target of Example 19 to obtain a modified Cu-K@Nafion protective film.
[0161] Example 23
[0162] The difference between Example 23 and Example 19 is that in Example 23, step S3 uses a high-purity (99.99%) Bi target material instead of the high-purity (99.99%) In target material of Example 19 to obtain a modified Bi-K@Nafion protective film.
[0163] Example 24
[0164] The difference between Example 24 and Example 19 is that in step S3 of Example 24, a high-purity (99.99%) Sb target is used instead of the high-purity (99.99%) In target of Example 19 to obtain a modified Sb-K@Nafion protective film.
[0165] Example 25
[0166] The difference between Example 25 and Example 19 is that in step S3 of Example 25, a high-purity (99.99%) Mg target is used instead of the high-purity (99.99%) In target of Example 19 to obtain a modified Mg-K@Nafion protective film.
[0167] Example 26
[0168] The difference between Example 26 and Example 19 is that in step S3 of Example 26, a high-purity (99.99%) Ni target is used instead of the high-purity (99.99%) In target of Example 19 to obtain a modified Ni-K@Nafion protective film.
[0169] Example 27
[0170] The difference between Example 27 and Example 19 is that in Example 27, step S3 uses a high-purity (99.99%) Mn target instead of the high-purity (99.99%) In target of Example 19 to obtain a modified Mn-K@Nafion protective film.
[0171] Example 28
[0172] The protective film in this embodiment is prepared by the following method:
[0173] S1. Cut Nafion NC700 to 60mm×60mm and peel off the surface film and bottom film of Nafion; place Nafion in a silicone oil bath at 70℃ and 5wt% H2O2 aqueous solution for 2 hours to remove organic impurities on the surface; rinse repeatedly with deionized water and then place in a silicone oil bath at 70℃ and deionized water for 2 hours to remove residual H2O2.
[0174] S2. After the water on the surface of Nafion was treated with lint-free paper, it was placed in 40 mL of 3 mol / L NaOH (aq) and left to stand for 48 h. After taking it out, it was washed three times with deionized water and dried in a 70℃ forced-air drying oven for 24 h to obtain Na@Nafion protective film.
[0175] S3. The dried Na@Nafion protective film is then subjected to an air pressure of less than 4×10⁻⁶. -4 In a high vacuum environment of Pa, using an 80W RF power supply and a high-purity (99.99%) In target, magnetron sputtering was performed for 3 hours at a sputtering pressure of 0.6Pa to obtain a modified In-Na@Nafion protective film.
[0176] FTIR characterization
[0177] Fourier transform infrared spectroscopy characterization of the samples was performed using a Renishaw inVia Reflex confocal micro-Raman spectrometer (UK). The test parameters were: SiC light source, DTGS detector, Michelson interferometer spectrometer system, and scanning range 4000–400 cm⁻¹. -1 Each image was scanned 32 times, with a wavenumber resolution of 4 cm⁻¹. -1 .
[0178] XPS characterization
[0179] The samples were characterized using a Kratos AXIS SUPRA X-ray photoelectron spectroscopy (XPS) instrument. The test parameters were: monochromatic AlK... α Light source (photon energy 1486.6 eV), power 150 W, ambient air pressure less than 5 × 10⁻⁶. -7 Torr has an X-ray focused beam size of 300 μm × 700 μm and a binding energy resolution of 0.45 eV.
[0180] Electrochemical performance testing
[0181] The battery performance testing instrument is manufactured by Wuhan Landian Electronics Co., Ltd., and its model number is CT2001A5V / 2mA.
[0182] The protective films of the examples and comparative examples were cut into... disc, Disc Cu foil as a current collector, A circular Zn wafer was used as the counter electrode. The electrolyte was a 140 μL 2 mol / L ZnSO4 aqueous solution. The separator was an 850 μm thick Watman GF / B glass fiber material. CR2032 button half-cells were assembled in the following order: Cu foil (+) || protective film (sputtered layer to Cu foil) || glass fiber separator + 140 μL 2 mol / L ZnSO4 (aq) || Zn foil (-). Cyclic performance testing was performed on the above cells. The areal capacity was 1 mAh·cm³. -2 Current density 1 mA·cm -2 The discharge cutoff voltage was 0V, and the charging cutoff voltage was 0.6V. The test results are shown in Table 1.
[0183] Will I2 / PAC plate as positive electrode, A CR2032 button cell was assembled using a disc-shaped Zn electrode as the negative electrode, a 140 μL 2 mol / L ZnSO4 aqueous solution as the electrolyte, and an 850 μm thick Watman GF / B glass fiber separator. The assembly sequence was I2 / PAC(+)||glass fiber separator + 140 μL 2 mol / L ZnSO4(aq)||protective film (sputtered layer facing Zn foil)||Zn foil(-). The cells were subjected to 0.5C (initial 4 cycles) / 3C rate cycling performance tests, with a discharge cutoff voltage of 0.6V and a charge cutoff voltage of 1.6V. The test results are shown in Table 1.
[0184] Table 1
[0185]
[0186]
[0187]
[0188] from Figure 1 It can be seen that after magnetron sputtering, a uniform and dense In film is formed on the surface of Na@Nafion;
[0189] from Figure 2 It can be seen that after magnetron sputtering In, the infrared characteristic peaks of most of the original groups on the Na@Nafion surface (except for a small number of CO2 peaks, 2340 and 2350 cm⁻¹) are restored. -1 The external signal is shielded on the In-Na@Nafion surface, indicating the density of the magnetron sputtered In coating;
[0190] from Figure 3 , Figure 4 , Figure 5As shown in Table 1, the aqueous zinc-ion battery equipped with the In-Na@Nafion protective film combines the advantages of cation exchange membranes and magnetron sputtering coatings during half-cell cycling, exhibiting long cycle life, high coulombic efficiency, and low polarization voltage. During full-cell cycling, it also demonstrates stable coulombic efficiency and high capacity retention. This demonstrates the effective role of this artificial zinc anode protective film in improving the cycle stability and reversibility of aqueous zinc-ion batteries.
[0191] As shown in Table 1, the proton exchange membrane of Comparative Example 1, without cation exchange treatment or magnetron sputtering, exhibits very low battery performance. While the proton exchange membranes of Comparative Examples 2-4 underwent cation exchange treatment, they did not undergo magnetron sputtering. The results show that their half-cell effective cycle count, coulombic efficiency, and full-cell capacity retention were improved compared to Comparative Example 1, but the first-cycle polarization voltage actually increased, indicating that cation exchange treatment alone is detrimental to reducing polarization. The proton exchange membranes of Comparative Examples 5-13, without cation exchange treatment but pretreated before direct magnetron sputtering of the metal layer, showed positive changes in half-cell effective cycle count, coulombic efficiency, and first-cycle polarization voltage compared to Comparative Example 1. However, the full-cell capacity retention of some metals decreased, suggesting that while magnetron sputtering alone improves some electrochemical performance, it may introduce adverse factors affecting capacity retention.
[0192] The proton exchange membranes of Examples 1-27, after pretreatment, cation exchange treatment, and magnetron sputtering, resulted in batteries that exhibited significantly better performance than batteries assembled with proton exchange membranes that were not cation exchange treated or magnetron sputtered. Among these, the proton exchange membranes treated with NaOH for cation exchange showed superior overall electrochemical performance compared to membranes treated with LiOH or KOH, exhibiting longer cycle life, higher coulombic efficiency, and better capacity retention. Furthermore, the proton exchange membranes with an In metal layer formed on their surface through magnetron sputtering demonstrated superior overall performance among various metals.
[0193] All aspects, embodiments, and features of this invention should be considered illustrative in all respects and not limiting of the invention; the scope of the invention is defined only by the claims. Other embodiments, modifications, and uses will become apparent to those skilled in the art without departing from the spirit and scope of the invention as claimed.
[0194] In the preparation method of this invention, the order of the steps is not limited to the listed order. For those skilled in the art, variations in the order of the steps without creative effort are also within the scope of protection of this invention. Furthermore, two or more steps or actions can be performed simultaneously.
[0195] Finally, it should be noted that the specific embodiments described herein are merely illustrative examples of the invention and are not intended to limit the implementation of the invention. Those skilled in the art can make various modifications or additions to the described specific embodiments or use similar methods to replace them; it is neither necessary nor possible to exemplify all embodiments here. However, these obvious variations or modifications derived from the essential spirit of the invention still fall within the scope of protection of the invention, and interpreting them as any additional limitation would contradict the spirit of the invention.
Claims
1. A protective film for the interface layer of a zinc metal anode, characterized in that, The protective membrane includes: at least one pretreated and cation exchange-treated proton exchange membrane and a metal layer located on the surface of the proton exchange membrane; The pretreatment includes: heating the proton exchange membrane in an aqueous hydrogen peroxide solution, removing it, and then heating it in water again; The cation exchange treatment includes: immersing the pretreated proton exchange membrane in a cation exchange solution, and cleaning and drying after the cation exchange is completed; The metal layer is formed from one or more of Al, Al-Si, Cu, Al-Si-Cu, Au, Au alloy, Ag, In, Fe, Co, Ni, Mn, Fe-Mn, Fe-Ni, Mg, Sn, Pb, Bi, Sb, Ti, Te, Zr, and Zn.
2. The zinc metal anode interface layer protective film according to claim 1, characterized in that, The proton exchange membrane is selected from one or more of the following: perfluorosulfonic acid proton exchange membrane, partially fluorinated proton exchange membrane, non-fluorinated sulfonic acid proton exchange membrane, and composite-enhanced proton exchange membrane.
3. The zinc metal anode interface layer protective film according to claim 1, characterized in that, The cation exchange solution is formed by dissolving a solute in water, and the solute is one or more of metal hydroxides, metal salts, metal halides, and metal sulfides. The metal in the metal hydroxide, metal salt, metal halide, and metal sulfide is selected from one or more of lithium, sodium, magnesium, potassium, calcium, manganese, iron, cobalt, nickel, copper, zinc, and silver. The metal salt is selected from one or more of the following metals: nitrates, sulfates, acetates, formates, phosphates, oxalates, borates, citrates, niobates, tetrafluoroborate, difluorooxalate borate, perchlorates, hexafluorophosphates, trifluoromethanesulfonates, iodates, bis(fluorosulfonyl)imide salts, arsenates, carbonates, and tantalates. The metal halide is selected from one or more of the chloride, fluoride, bromide, and iodide of the metal.
4. A zinc metal anode interface layer protective film according to claim 1 or 3, characterized in that, The solute in the cation exchange solution is one or more of LiOH, NaOH, and KOH; And / or, the concentration of the cation exchange solution is 0.1–5 mol / L; And / or, the soaking time is 12 to 72 hours; And / or, the drying temperature is 40–100°C, and the drying time is 12–48 h.
5. The zinc metal anode interface layer protective film according to claim 1, characterized in that, The proton exchange membrane is selected from one or more of the Nafion series of perfluorosulfonic acid membranes; And / or, the metal layer is formed of one or more of Al, In, Sn, Cu, Bi, Sb, Mg, Ni, and Mn.
6. The zinc metal anode interface layer protective film according to claim 1, characterized in that, The metal layer is obtained by magnetron sputtering, which includes the following steps: In a vacuum environment, a magnetron sputtering target is excited by a radio frequency power supply to form a metal layer on the surface of a proton exchange membrane after cation exchange.
7. The zinc metal anode interface layer protective film according to claim 1, characterized in that, The vacuum environment pressure is 0.1~9×10 -4 Pa; And / or, the power of the radio frequency power supply is 10-150W, and the sputtering pressure is 0.1-1.0Pa; And / or, the magnetron sputtering duration is 0.5 to 5 hours; And / or, the magnetron sputtering target material is an alloy formed from one or more of Al, Al-Si, Cu, Al-Si-Cu, Au, Au alloy, Ag, In, Fe, Co, Ni, Mn, Fe-Mn, Fe-Ni, Mg, Sn, Pb, Bi, Sb, Ti, Te, Zr, and Zn.
8. The method for preparing a zinc metal anode interface layer protective film as described in claim 1, characterized in that, Includes the following steps: The proton exchange membrane was heated in a hydrogen peroxide aqueous solution, then removed and heated in water again. After removing the surface moisture of the proton exchange membrane, it was immersed in a cation exchange solution. After cation exchange was completed, it was cleaned and dried. In a vacuum environment, a magnetron sputtering target was excited by a radio frequency power supply to form a metal layer on the surface of the proton exchange membrane after cation exchange.
9. An aqueous zinc-ion battery, characterized in that, The aqueous zinc-ion battery includes at least one protective film as described in claim 1.
10. An aqueous zinc-ion battery according to claim 9, characterized in that, The aqueous zinc-ion battery is either a half-cell or a full-cell aqueous zinc-ion battery. In the aqueous zinc-ion battery half-cell, the protective film is located between the negative electrode and the separator, and / or between the current collector and the separator; In the aqueous zinc-ion battery full cell, the protective film is located between the negative electrode and the separator, and the side of the protective film with the metal layer faces the electrode.
